Feasibility, and barriers to use escitalopram in functional gastrointestinal disorders - Alkhowaiter, Saad S.; Alshahrani, Amani H.; Almarzouqi, Hala F.; Alonazi, Gadah K.; Alhawassi, Tariq M.; AlRasheed, Maha M. (Frontiers in Pharmacology, 2023)
Background and study aims: The feasibility and barriars of escitalopram use in patients with functional gastrointestinal disorders (FGIDs) are still debated. We aimed to evaluate the feasibility, safety and efficacy and barriars of escitalopram use in managing FGIDs in the Saudi population. Patients and Methods: We included 51 patients who received escitalopram for irritable bowel syndrome (n= 26), functional heartburn (n= 10), globus sensation (n= 10) or combined disorders (n= 5). We used an irritable bowel syndrome- severity scoring system IBS-SSS), GerdQ questionnaire and Glasgow Edinburgh Throat Scale (GETS) to assess disease severity change before and after treatment. Results: The median age was 33 years (25th- 75th percentiles: 29- 47), and 26 (50.98%) were males. Forty-one patients experienced side effects (80.39%), but most side effects were mild. The most common side effects were drowsiness/fatigue/dizziness (54.9%), xerostomia (23.53%), nausea/vomiting (21.57%) and weight gain (17.65%). IBS-SSS was 375 (255-430) and 90 (58- 205) before and after treatment, respectively (P <0.001). GerdQ score was 12 (10- 13) before treatment and 7 (6-10) after treatment (P= 0.001). GETS score before treatment was 32.5 (21- 46) and after treatment became 22 (13-31) (P= 0.002). Thirty-five patients refused to take the medications, and seven patients discontinued the medication. Possible causes of the poor compliance were fear of the medications and not being convinced of taking psychiatric medications for functional disorders (n= 15). Conclusion: Escitalopram could be a safe and effective treatment for functional gastrointestinal disorders. Targeting and managing factors leading to poor compliance could further improve the treatment outcome.